Association of serum vitamin D3 levels and oral diseases - Systematic Review (Research, Society and Development, 2021)
The active metabolite of vitamin D3, cholecalciferol, is a multifunctional hormone that acts in the regulation of calcium and phosphorus homeostasis and which, in addition, has shown promising results as an immunomodulator, an antitumor agent, among other functions. Therefore, this systematic review aims to review in the scientific literature how cholecalciferol acts as a hormonal modulator and what is its role in oral pathologies. A search was carried out in the PubMed (MEDLINE), Scopus, Embase, Google Scholar and The Cochrane Library databases, having as inclusion criteria studies which will use issues related to oral health associated with the use of cholecalciferol. We found several oral pathologies that are associated with cholecalciferol, and we verified its role in inflammation, chemoprevention and as an antitumor agent, we also revealed that low levels of this vitamin are associated with the appearance and/or predisposition of oral pathologies. We conclude that maintaining optimal serum cholecalciferol levels is very important for the preservation and maintenance of oral health as well as systemic health.